2010
DOI: 10.1016/j.jmatprotec.2010.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The heat treatment of Al–Si–Cu–Mg casting alloys

Abstract: Environmental savings can be made by increasing the use of aluminium alloys in the automotive industry as the vehicles can be made lighter. Increasing the knowledge about the heat treatment process is one task in the direction towards this goal. The aim of this work is to investigate and model the heat treatment process for Al-Si casting alloys. Three alloys containing Mg and/or Cu were cast using the gradient solidification technique to achieve three different coarsenesses of the microstructure and a low amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
223
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(281 citation statements)
references
References 83 publications
(93 reference statements)
6
223
0
4
Order By: Relevance
“…The increase in Cu concentration in the dendrite center, illustrated in Figure 3(a) could be a consequence of dissolution of Al2Cu phase (the most abundant intermetallic) or fragmentation of other Cu-bearing phases such as Q-Al5Mg8Si6Cu2, which is noted in other studies [7,26]. A large fraction of the Al2Cu phases in the 10 μm microstructure dissolved at 500 ºC, and the solute concentration reaches 2.22 wt.…”
Section: Cu-and Mg-bearing Phasesmentioning
confidence: 52%
See 1 more Smart Citation
“…The increase in Cu concentration in the dendrite center, illustrated in Figure 3(a) could be a consequence of dissolution of Al2Cu phase (the most abundant intermetallic) or fragmentation of other Cu-bearing phases such as Q-Al5Mg8Si6Cu2, which is noted in other studies [7,26]. A large fraction of the Al2Cu phases in the 10 μm microstructure dissolved at 500 ºC, and the solute concentration reaches 2.22 wt.…”
Section: Cu-and Mg-bearing Phasesmentioning
confidence: 52%
“…Si precipitates from the as-cast super saturated solid solution during aging at temperatures range of 200-250 °C [6]. High temperature exposure of Al-Si-Cu-Mg alloys may lead to changes in the concentrations of alloying elements and of vacancies in solid solution, and to spheroidization of Si particles [7]. The dissolution rate of the various secondary phases is dependent on time and temperature of the exposure, the chemical composition and coarseness of the microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…The Figure 7c illustrates a close up of these precipitates which have been reported partially coherent and metastable phases with body-centered tetragonal crystal structure. The lattice parameters are a=b=0.406 nm, c=0.58 nm and space group I4/mcm 2,24,26,27 . The Figure 7b illustrates EDS elemental microanalyses of aluminum matrix and acicular precipitates and confirms the presence of Cu and Al in these precipitated phases.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…The effects of heat treatments in Al-Si-Cu alloys have been studied by different techniques from different authors 1,2,6,7 . The authors reported that β-Mg 2 Si, θ-Al 2 Cu, Al 2 CuMg, and Al 4 CuMg 5 Si 4 phases are dissolved during the SHT and are highly responsible of hardening of Al-Si-Cu-Mg, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Standard heat treatment of the silumins, comprising copper and magnesium additions, is precipitation hardening, consisting of two operations: solutioning and artificial or natural ageing [6], what enables much better mechanical properties of the castings with simultaneous decrease of the elongation and ductility [7,8,9].…”
Section: Introductionmentioning
confidence: 99%